Dawabith al-Mashlahah - Bahtiar Hasan (NALAR FIQH: Jurnal Hukum Islam, 2011)
This article tried to collect literature to find the data about sharia, fiqih and terms related with it. The data have been collected were analized using descriptive language approach, sociological approach and historical approach. Language approach be used to describe the term of sharia and fiqih as a base of development. The sociological approach be used to disclosed the sharia andsocial contexs and historical approach to see the progress sharia and fiqih in terms of historical aspects.